The Mediating Effects of Stigma on Depressive Symptoms in Patients With Tuberculosis: A Structural Equation Modeling Approach - Qiu, Lei; Yang, Qin; Tong, Yeqing; Lu, Zuxun; Gong, Yanhong; Yin, Xiaoxv (Frontiers in Psychiatry, 2018)
Objectives: To date, the complex interrelationships between family function, doctor-patient communication, knowledge about tuberculosis (TB), stigma, and depressive symptoms among patients with TB are insufficiently understood. We explored the interrelationships between family function, doctor-patient communication, knowledge about TB, stigma and depressive symptoms and examined whether stigma played a mediating role. Methods: A cross-sectional survey was conducted between October 1, 2013 and March 31, 2014 in Hubei province, central China. Data were collected from 1,309 patients using a structured questionnaire that measured family function, doctor-patient communication, knowledge about TB, stigma, and depressive symptoms. Structural equation modelling was used to examine the interrelationships among the study variables based on the hypothesized model. Results: The proposed model provided a good fit to the obtained data. There were indirect effects between family function, doctor-patient communication, knowledge about TB, and depressive symptoms through stigma (β = -0.048, P = .002; β = -0.028, P = .001; β = -0.021, P = .009, respectively). Stigma partially mediated the effect of family function and knowledge about TB on depressive symptoms and fully mediated the effect of doctor-patient communication on depressive symptoms. Conclusions: This study elucidated the pathways linking family function, doctor-patient communication, and knowledge about TB to depressive symptoms and confirmed that the effect of those variables on depressive symptoms can be mediated by stigma. Those findings provide direction and information for depression interventions among patients with TB.